Economic policy and economical production - A. D. Kuzmichev (Мир новой экономики, 2018)
Article shows the two poles of the debates about economic policy - the supporters of the liberal market concept and those who propose other models of development, aimed at creating conditions for improving the formation of the basic industries of the new technological order. The experience of the Kaluga region on creation of a new economic order is illuminated. Horizontal and vertical tools of industrial policy are specified. Programs of development of lean production are presented, the experience of the creation of new production systems in Russian companies is considered.